Proteomic Dissection of Seed Germination and Seedling Establishment in Brassica napus - Gu, Jianwei; Chao, Hongbo; Gan, Lu; Guo, Liangxing; Zhang, Kai; Li, Yonghong; Wang, Hao; Raboanatahiry, Nadia; Li, Maoteng (Frontiers in Plant Science, 2016)
The success of seed germination and the establishment of a normal seedling are key determinants of plant species propagation. At present, only few studies have focused on the genetic control of the seed germination by proteomic approach in Brassica napus. In the present study, the protein expression pattern of seed germination was investigated using differential fluorescence two-dimensional gel electrophoresis (2-D DIGE) in B. napus. One hundred thirteen differentially expressed proteins (DEPs), which were mainly involved in storage proteins (23.4%), energy metabolism (18.9%), protein metabolism (16.2%), defense/disease (12.6%), seed maturation (11.7%), carbohydrate metabolism (4.5%), lipid metabolism (4.5%), amino acids metabolism (3.6%), cell growth/division (3.6%), and some unclear proteins (2.7%) were observed by proteomic analysis. Seventeen genes corresponding to 11 DEPs were identified within or near the associated linkage disequilibrium regions related to seed germination and vigor quantitative traits reported in B. napus in previous studies. The expression pattern of proteins showed the heterotrophic metabolism could be activated in the process of seed germination and the onset of defense system might start during seed germination. These findings will help us more in-depth understanding of the mobilization of seed storage reserves and regulation mechanisms of germination process in B. napus.